Improved durability of 3D-printed ear tags for virtual fencing in cattle: mechanical and field performance - Hannah James; Clara Rial; Darke Hull; Jamison Taylor; Theopisti Nikolaou; Juan Boza; Julio Giordano; David Erickson (Frontiers in Animal Science)
Livestock tracking technologies, particularly virtual fencing systems which confine animals within a designated area without physical fences, have seen significant advancements. However, much of the research focuses on the technology and functionality of these systems, and less attention has been given to the materials used in their design, which are critical to their long-term effectiveness and durability. Specifically, there is a lack of research on optimized materials and designs for cow virtual fencing devices, despite their essential role in ensuring reliable cattle tracking and enhancing animal welfare. Durable, non-toxic materials capable of withstanding harsh environmental conditions are crucial for these applications, yet limited studies have explored suitable material options. This study addresses this gap through a three-pronged approach combining Finite Element Analysis (FEA) simulations, mechanical analysis, and field testing to evaluate two prototype cow ear tag designs—one made from high-speed resin and the other from Nylon 6/66. This study examines their performance under simulated real-world factors, such as chewing forces and environmental exposure. In addition, we conducted field tests at the Cornell University Ruminant Center, a large-scale research dairy facility, to evaluate the prototypes under operational farm conditions. Our findings demonstrate that material choice, and weight significantly affect device longevity, with a reduced size and weight Nylon material offering a 50% improvement in durability compared to resin. Our results emphasize how important material and design choices are in the wider application of sustainable and precision agriculture practices.